Modeling the Effect of Modified Atmospheres on Conidial Germination of Fungi from Dairy Foods - Nguyen Van Long, Nicolas; Vasseur, Valérie; Couvert, Olivier; Coroller, Louis; Burlot, Marion; Rigalma, Karim; Mounier, Jérôme (Frontiers in Microbiology, 2017)
Modified atmosphere packaging (MAP) is commonly applied to extend food shelf-life. Despite growth of a wide variety of fungal contaminants has been previously studied in relation to modified-atmospheres, few studies aimed at quantifying the effects of dioxygen (O2) and carbon dioxide (CO2) partial pressures on conidial germination in solid agar medium. In the present study, an original culture method was developed, allowing microscopic monitoring of conidial germination under modified-atmospheres in static conditions. An asymmetric model was utilized to describe germination kinetics of Paecilomyces niveus, Mucor lanceolatus, Penicillium brevicompactum, Penicillium expansum and Penicillium roquefoti, using two main parameters, i.e., median germination time (τ) and maximum germination percentage (Pmax). These two parameters were subsequently modelled as a function of O2 partial pressure ranging from 0 % to 21 % and CO2 partial pressure ranging from 0.03 % to 70 % (8 tested levels for both O2 and CO2). Modified atmospheres with residual O2 or CO2 partial pressures below 1% and up to 70 %, respectively, were not sufficient to totally inhibit conidial germination,. However, O2 levels < 1% or CO2 levels > 20% significantly increased τ and/or reduced Pmax, depending on the fungal species. Overall, the present method and results are of interest for predictive mycology applied to fungal spoilage of MAP food products.